The first year: Journal of Society of Anesthesiologists of Nepal (JSAN) - Sharma, Apurb; Pradhan, Bishwas (Journal of Society of Anesthesiologists of Nepal, 2015)
Abstract not available Journal of Society of Anesthesiologists of Nepal 2015; 2(1): 1